Tranexamic acid is safe to use following mild-to-moderate traumatic brain injury. (11th March 2020) - Cook, Rob; Lyon-Maris, Johnny; Martin, Rosie
The study: The CRASH-3 Trial Collaborators. Effects of tranexamic acid on death, disability, vascular occlusive events and other morbidities in patients with acute traumatic brain injury (CRASH-3): a randomised, placebo-controlled trial. Lancet 2019;394:1713-23. This trial was funded by NIHR Health Technology Assessment Programme (project number 14/190/01), JP Moulton Charitable Trust, Department of Health and Social Care, Department for International Development, Global Challenges Research Fund, Medical Research Council, and the Wellcome Trust (Joint Global Health Trials scheme). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000870/tranexamic-acid-following-mild-to-moderate-traumatic-brain-injury-is-safe-and-reduces-deaths